"I Want to Full My Tank": An Autoethnographic Reflection on the Use of Language and the Identity at Risk. (April 2015) - Merlino, Aldo
In this autoethnographical essay, I focus on the difficulties related to improper use of a second language. I show how such misuse contributes to the attribution of personality qualities to the speaker and, consequently, how the identity of the speaker gets lost and replaced by a new (acoustic) identity. Such acoustic identity is given by pragmatic failures that emerge when people speak a second language.